SURVEI MINAT MASYARAKAT TERHADAP PEMANFAATAN RUANG TERBUKA PUBLIK SEBAGAI TEMPAT BEROLAHRAGA DI KOTA SALATIGA TAHUN 2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2015)
This study aims to determine the Salatiga public interest in utilizing public open space as a place to work out in the 2013.The technique to obtain data that is by spreading the sample questionnaire respondents from each age category, the group of children under 15 years, adolescents with age between 15-25 years, adults between the ages of 26-50 years, and older people over the age of 50 years a total of 200 people. The results showed that the public interest in the use of public open space as a place to work out in Salatiga was 76.14 % for the children category, amounting to 74.42 % for the teen category, amounting to 82.08 % for the adult category, and amounted to 76.86 % for the parent category. It can be concluded that the public interest in the use of public open space as a place to work out in Salatiga in 2013 in high categorized or interested . Adult age category ( 26-50 years ) had the highest percentage of interest in the use of public open space as a place to work out in Salatiga in 2013.